Occupation-congruent appearance: a measuremental approach - Sarpila Outi; Koivula Aki; Kukkonen Iida (Turun yliopisto, 2022)
In this article we introduce a novel measure, which we call ‘occupation-congruent appearance’ (OCA). We argue that the measure captures the appearance norms of looking ‘right’ for a particular occupation. Using a combination of large-scale photograph data (N=1,411) and rating data (N=7,920) from Finland, including 387,542 individual ratings, we show that shared cultural standards for OCA exist, and rate of agreement compares with agreement on beauty standards. We systematically compare the relationship between OCA, attractiveness, and masculinity/femininity in male-dominated, gender-balanced, and female-dominated occupational fields for men and for women. We conclude that occupation-congruent appearance is independent from other typically used measures in studies on appearance and social inequalities. Thus, it seems that OCA can capture the kind of elements of appearance that are not reducible to attractiveness, femininity, and masculinity. We discuss the possibilities for using OCA as a complementary measure for researchers interested in appearance and social inequalities.